ナンキョク エンコ ノ カガクテキ トクチョウ - 鳥居, 鉄也; トリイ, テツヤ; 山県, 登; ヤマガタ, ノボル; 中谷, 周; ナカヤ, シュウ; 村田, 貞雄; ムラタ, サダオ; TORII, Tetsuya; YAMAGATA, Noboru; NAKAYA, Shyu; MURATA, Sadao (国立極地研究所, 1977)
P(論文) 南極大陸の露岩地域には多くの湖沼が存在するが,その塩分濃度あるいは化学組成にはさまざまな特徴がみられる.この報告は,昭和,マクマード,ベストフォールドの各オアシスの湖沼調査から,とくに塩湖の化学的特徴を中心として述べたものである.南極の塩湖は,沿岸地域と山岳地域のものとに大別されるが,前者は一般に湖面高度が海面下にあって,地形上からも,また水質や湖岸堆積物などの化学的特徴からみても海跡湖とみられるものが多い.一方,山岳地域のものは,旧湖岸線も存在し湖水面が過去に大きく変動し,湖水がくりかえし濃縮されたことを示唆するが,水質が海水と異なって単純に塩分の起因を説明しえない.しかし,最近実施されたDVDP調査の結果から,これら山岳地域の塩湖も塩類の大部分は海水に由来し,その後変質したと考えられるに至った.そして水質の考察から,沿岸地域のものより一般に古い歴史をもつものと推定される. Chemical characteristics of main Antarctic saline lakes found in the oases of McMurdo. Vestfold and Syowa are reviewed. Lakes are primarily classified into the fresh and saline ones and then the latter into coastal lakes and those located in the glacial trough such as the Dry Valleys, Victoria Land. The coastal saline lakes are characterized by that the elevation of lake surface is below sea level and the chemical composition, such as M/C1 ratio, isotopic ratio of oxygen and hydrogen, and also the nutrient elements resemble those of sea water, while the saline lakes in the Dry Valleys have a complex origin. From the geochemical point of view, it is suggested that the formation of the coastal lakes is much younger than that of the lakes in the Dry Valleys. departmental bulletin paper